PROBLEMS OF FORMATION AND OPTIMIZATION OF RESOURCE PROVISION OF ENTERPRISES IN THE CONDITIONS OF FINANCIAL CONSTRAINTS - S. Demin; A. Zinchenko; L. Uglova (Вестник университета)
In the article the approach to formation of resource support in industrial enterprises, aiming at the optimisation of funding and achievement of high efficiency of production. The application of the approach in practice allows to obtain predictions and make management decisions, adequate to the objectives and to carry out coordinating functions by regulating the degree of importance of the values of indicators of resource provision